Thermal Comfort in Zero Energy Buildings. (October 2017) - Pomfret, Laura; Hashemi, Arman
Abstract: This paper evaluates thermal comfort in domestic zero energy buildings. Dynamic simulations are used to assess a variation of scenarios including: construction types, natural ventilation strategies, solar shading, and occupancy periods in a low energy case study dwelling, within the United Kingdom. The Chartered Institution of Building Services Engineers Technical Memoranda 52 (CIBSE TM52) is used to evaluate the thermal comfort conditions, and the state of overheating within the case study dwelling. The results indicate that increasing the thermal mass of the external walls significantly reduces the risk of overheating within the case study dwelling. Additionally, the most beneficial window opening profile is night ventilation. The addition of solar shading on the South, East and West elevations considerably improved thermal comfort conditions. Increasing the effective openable glazing area to facilitate natural ventilation in zero energy buildings and further improve the indoor thermal comfort.